2022
DOI: 10.1002/ps.7048
|View full text |Cite
|
Sign up to set email alerts
|

Towards intelligent and integrated pest management through an AIoT‐based monitoring system

Abstract: BACKGROUND Main bottleneck in facilitating integrated pest management (IPM) is the unavailability of reliable and immediate crop damage data. Without sufficient insect pest and plant disease information, farm managers are unable to make proper decisions to prevent crop damage. This work aims to present how an integrated system was able to drive farm managers towards sustainable and data‐driven IPM. RESULTS A system called Intelligent and Integrated Pest and Disease Management (I2PDM) system was developed. Edge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The I 2 PDM system is composed of an intelligent integrated pest management wireless sensor network that collects images, pest numbers, and species through sensor nodes and stores them in a database for analysis, thus generating models that can be visually translated into numerical information (Rustia et al 2020). The technique was applied to a tomato field, and the pesticide dose was reduced from 235 to 204 L/time (16%), indicating that insecticide spraying effectively reduced pests (Rustia et al 2022).…”
Section: Using Artificial Intelligence For Precision Agriculture To R...mentioning
confidence: 99%
“…The I 2 PDM system is composed of an intelligent integrated pest management wireless sensor network that collects images, pest numbers, and species through sensor nodes and stores them in a database for analysis, thus generating models that can be visually translated into numerical information (Rustia et al 2020). The technique was applied to a tomato field, and the pesticide dose was reduced from 235 to 204 L/time (16%), indicating that insecticide spraying effectively reduced pests (Rustia et al 2022).…”
Section: Using Artificial Intelligence For Precision Agriculture To R...mentioning
confidence: 99%
“…PA's data-driven insights into soil conditions, microclimates, and plant health can serve to inform IPM strategies, allowing for more targeted and effective pest control measures [59]. For instance, drone technology equipped with multispectral cameras can provide real-time data on pest infestations, enabling timely interventions that align with IPM principles [12].…”
Section: Convergence Of Precision Agriculture and Integrated Pest Man...mentioning
confidence: 99%
“…Recent studies have demonstrated that the integration of these two approaches leads to more efficient resource utilization, lower pesticide use, and improved crop yield [10,11]. For instance, a study [12] found that utilizing drone technology for pest monitoring in an IPM framework resulted in a 30% reduction in pesticide use. Similarly, [13] observed that soil sensors used for real-time monitoring of soil moisture and nutrient levels could significantly enhance the efficiency of IPM strategies.…”
Section: Introductionmentioning
confidence: 99%
“…There are two digital approaches in monitoring insect pests: automated and semiautomated. A fully automated approach entails the use of wireless sensor nodes, which are equipped with cameras that capture sticky paper trap images [10]. The sticky paper trap images are analyzed locally or through cloud computing.…”
Section: Introductionmentioning
confidence: 99%